2000
DOI: 10.1016/s0925-4439(99)00080-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of macrophage migration inhibitory factor (MIF) expression in injured epidermis and cultured fibroblasts

Abstract: After the cDNA of human macrophage migration inhibitory factor (MIF) was cloned in 1989, this protein has been re-evaluated as a pro-inflammatory cytokine, pituitary hormone and glucocorticoid-induced immunoregulatory protein. We previously reported the expression of MIF in the basal cell layers of the epidermis, but its pathophysiological function in the skin has not been well understood. In this study, we examined the expression of MIF during the wound healing of rat skin injured by excision. Reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 29 publications
9
72
1
Order By: Relevance
“…We examined the wound healing ability of mice at 6 weeks after vaccination, and found no statistical difference between MIF/TTX group and control group. Abe et al 33 previously reported that the administration of anti-MIF antibody resulted in significantly delayed wound healing in C57BL6 mice; however, we failed to show such significant difference, although MIF/TTX group tended to show slight delay in wound healing. Concerning this discrepancy, it is known that the wound healing ability of mice are influenced by their strain, and BALB/c mice generally tend to show delayed wound healing compared with C57BL6.…”
Section: Mif/ttx Dna Vaccination and Sepsis S Tohyama Et Alcontrasting
confidence: 90%
“…We examined the wound healing ability of mice at 6 weeks after vaccination, and found no statistical difference between MIF/TTX group and control group. Abe et al 33 previously reported that the administration of anti-MIF antibody resulted in significantly delayed wound healing in C57BL6 mice; however, we failed to show such significant difference, although MIF/TTX group tended to show slight delay in wound healing. Concerning this discrepancy, it is known that the wound healing ability of mice are influenced by their strain, and BALB/c mice generally tend to show delayed wound healing compared with C57BL6.…”
Section: Mif/ttx Dna Vaccination and Sepsis S Tohyama Et Alcontrasting
confidence: 90%
“…In summary, judging from the previous data by the Ashcroft and Nishihira groups [13][14][15][16] in conjunction with our current study, we predict that MIF contributes to both the inflammatory and migration/proliferation phases of wound healing. We propose the following chronology of events involving MIF.…”
Section: Discussionsupporting
confidence: 70%
“…Estrogen-mediated down-regulation of MIF and protection from MIF-dependent inflammatory processes was recently confirmed in a model of colon inflammation [30]. On the other hand, Abe and colleagues observed that an upregulation of MIF in skin wounds of rats was accompanied by an accelerating effect of MIF on the wound healing process of skin tissue [15]. On first sight contradictory, these observations may suggest that MIF influences more than one mechanism contributing to wound healing outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The primary focus of MIF research has been in the context of its role in immunological function, and studies that used pure recombinant MIF and MIF-specific antibodies have established a role of MIF in the pathogenesis of septic shock (3), inflammatory arthritis (4), glomerulonephritis (5), allograft rejection (6), and wound repair (7). At the cellular level, MIF has been reported to antagonize the action of glucocorticoids and to promote the production of proinflammatory mediators (reviewed in ref.…”
Section: Macrophage Migration Inhibitory Factor (Mif) Ismentioning
confidence: 99%